Resolution of the phosphotransferase enzymes of Streptococcus mutans: purification and preliminary characterization of a heat-stable phosphocarrier protein. - Mimura, C S (1984)
The sucrose phosphotransferase system of Streptococcus mutans catalyzes the phosphorylation of sucrose to sucrose-6-phosphate with concomitant translocation of this disaccharide across the cytoplasmic membrane in reactions requiring intracellular phosphoenolpyruvate. Soluble proteins released by vigorous homogenization of cells with glass beads are shown to be necessary for the phosphoenolpyruvate-dependent phosphorylation of sucrose in combination with one or more proteins that remain tightly associated with the membrane fraction. We have partially purified phosphotransferase enzyme I and have purified a heat-stable phosphocarrier protein (HPr) to apparent homogeneity, by gel filtration and ion-exchange chromatography from the soluble fraction. HPr from S. mutans has an apparent molecular weight larger than that of Escherichia coli HPr but has properties similar to those of Staphylococcus aureus HPr. Furthermore, it appears to be partially complexed with a heat-stable enzyme III-like protein in cell-free fractions from S. mutans, and we also report the purification of this complex. Enzyme I from S. mutans is a protein (native Mr greater than 100,000) that cross-complements enzyme I from S. aureus. Preliminary characterizations of homogeneous HPr and its complex with the putative enzyme III are also presented.